Metallogenic Setting and Evolution of the Pados-Tundra Cr-Bearing Ultramafic Complex, Kola Peninsula: Evidence from Sm–Nd and U–Pb Isotopes - Pavel A. Serov; Tamara B. Bayanova; Ekaterina N. Steshenko; Evgeniy L. Kunakkuzin; Elena S. Borisenko (Minerals, 2020)
The article presents new Sm–Nd and U–Pb geochronological data on rocks of the poorly studied Pados-Tundra Cr-bearing complex. It is part of the Notozero mafic–ultramafic complex (western Kola Peninsula) and occurs at the border of the Paleoproterozoic Lapland Granulite Belt and the Archean Belomorian composite terrain. The Pados-Tundra complex hosts two major zones, the Dunite and Orthopyroxenite Blocks. Dunites are associated with four levels of chromite mineralization. Isotope Sm–Nd studies of dunites, harzburgites, and orthopyroxenites from the central part of the complex have been carried out. The isochron Sm–Nd age on 11 whole-rock samples from a rhythmically layered series of the complex is 2485 ± 38 Ma; the mineral Sm–Nd isochron for harzburgites shows the age of 2475 ± 38 Ma. It corresponds with the time of large-scale rifting that originated in the Fennoscandian Shield. When the rhythmically layered series of the intrusion and its chromite mineralization were formed, hornblendite dykes intruded. The U–Pb and Sm–Nd research has estimated their age at ca. 2080 Ma, which is likely to correspond with the occurrence of the Lapland–Kola Ocean. According to isotope Sm–Nd dating on metamorphic minerals (rutile, amphibole), the age of postmetamorphic cooling of rocks in the complex to 650–600 °C is 1872 ± 76 Ma. The U–Pb age on rutile from a hornblendite dyke (1804 ± 10 Ma) indicates further cooling to 450–400 °C. The conducted research has determined the early Proterozoic age of rocks in the rhythmically layered series in the Pados-Tundra complex. It is close to the age of the Paleoproterozoic ore magmatic system in the Fennoscandian Shield that developed 2.53–2.40 Ga ago. Later episodes of alterations in rocks are directly related to main metamorphic episodes in the region at the turn of 1.9 Ga. Results of the current study expand the geography of the vast Paleoproterozoic East Scandinavian Large Igneous Province and can be applied for further studies of similar mafic–ultramafic complexes.